2021
DOI: 10.1371/journal.pone.0251315
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive mild traumatic brain injury affects inflammation and excitotoxic mRNA expression at acute and chronic time-points

Abstract: The cumulative effect of mild traumatic brain injuries (mTBI) can result in chronic neurological damage, however the molecular mechanisms underpinning this detriment require further investigation. A closed head weight drop model that replicates the biomechanics and head acceleration forces of human mTBI was used to provide an exploration of the acute and chronic outcomes following single and repeated impacts. Adult male C57BL/6J mice were randomly assigned into one of four impact groups (control; one, five and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 95 publications
1
17
0
Order By: Relevance
“…4B ). Following smTBI, GFAP was reported to marginally increase in the hours after smTBI (61,75,79,83,90), and then return to sham values between 2-7d post-injury (56,60,63). There was an exception in one study using a weight drop injury model that reported increased GFAP levels at 30d post-injury (73).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B ). Following smTBI, GFAP was reported to marginally increase in the hours after smTBI (61,75,79,83,90), and then return to sham values between 2-7d post-injury (56,60,63). There was an exception in one study using a weight drop injury model that reported increased GFAP levels at 30d post-injury (73).…”
Section: Resultsmentioning
confidence: 99%
“…There was an exception in one study using a weight drop injury model that reported increased GFAP levels at 30d post-injury (73). In rmTBI models, GFAP was assessed at ’hours’ in 5 studies (42,56,66,81,83), at ’days’ in 3 studies (42,63,93), at ’weeks’ in 2 studies (42,66), and at ’months’ in 3 studies (63,88,92) ( Fig. 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…From a biological point of view, the significance of this finding could be very high because, although rescue of TDP-43 pathology did not occur in a yeast model of disease following ablation of the homologous yeast gene (Aif1p) ( 56 ), elevated levels of this factor have been observed in specific molecular subtypes of ALS patients ( 57 ), in the cortex of mice subjected to mild traumatic brain injury ( 58 ), and very recently in Atxn-CAG100 knock-in mice that eventually develop TDP-43 pathology ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aif1 is a calcium-binding protein that regulates immune and inflammatory responses [58,59]. Increased expression of Aif1 is an indication of microglia and macrophage activation in response to brain trauma [60,61]. A previous experimental study identified Trem2 and Tyrobp as significant hub genes in TBI mice expressing human APOE [62].…”
Section: Discussionmentioning
confidence: 99%